White Eminence and the Case for Responsible Freedom - Collier, Natalie A (Prabuddha: Journal of Social Equality; Vol 2 No 1 (2018): Myths underlying brahmin supremacy and white supremacy, 2018)
White supremacy is a ubiquitous ideology that can surreptitiously greet us, like sunrise in the morning does after yet another night of insomnia, or can punch us squarely on the jaw with brass knuckles after an impassioned lesson about the virtues of turning the other cheek. Micro- and macro-presentations of white supremacy, othering and socio-political phobias are direct results of the insecurities and laziness of colonialists and their contemporary progeny, neocolonialists. Whichever way it shows up (and it does relentlessly, surviving on something more than oxygen), this so-called supremacy and those committed to working on its behalf inherently resist freedom. Conversely, autonomy is inevitable when we take for ourselves the chief components of what is necessary for any deep-rooted infrastructure, personal or otherwise: space and time. Taking space and time to learn, strategize, explore and create—individually and cooperatively—are essential to persevere and overturn an intangible, inescapable ideology meant to snuff out our very life force.